77-9y=23

Simple and best practice solution for 77-9y=23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 77-9y=23 equation:


Simplifying
77 + -9y = 23

Solving
77 + -9y = 23

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-77' to each side of the equation.
77 + -77 + -9y = 23 + -77

Combine like terms: 77 + -77 = 0
0 + -9y = 23 + -77
-9y = 23 + -77

Combine like terms: 23 + -77 = -54
-9y = -54

Divide each side by '-9'.
y = 6

Simplifying
y = 6

See similar equations:

| x=38.34x+0.50 | | 15=-.6n | | 3x+5+3y+108=180 | | 4(x+5)=5(3x-7) | | 3*4-8=8 | | x+5=y-50 | | 8x-6=32 | | 3x+5+37+108=180 | | 15-x=5.2 | | 5b+40=20b+40 | | 8+m=9m-7 | | -z+6=-6 | | 5b+40=200b+400 | | 60-5x=22x+18 | | 2x=7y-11 | | 4x+4x=23x | | y/78+93=95 | | (7)-(14)= | | 3x+15+8=3x+15 | | 3f-8=f | | 3(2y-1)-y=2(y+2)-(y-4) | | (44-x)-2=3x-6 | | -22-6x=-9x | | -910=-26a | | 4(n-3)-2(n+2)=3(n+5)-n | | a+x=t | | x^2-4k+1=-5 | | 60=6(6-2x) | | 5x+7=3x+3 | | 11x+5=15+10x | | 3x^4=360 | | f+3=15 |

Equations solver categories